Association Between Prolonged Grief and Attitudes Toward Reconciliation in Bereaved Survivors of the Khmer Rouge Regime in Cambodia - Stammel, Nadine; Heinzl, Louisa; Heeke, Carina; Böttche, Maria; Knaevelsrud, Christine (Frontiers in Psychiatry, 2020)
During the Khmer Rouge regime in Cambodia, about a quarter of the population died, resulting in many individuals losing close relatives. Still today, many individuals are suffering from the psychological consequences of these losses, which might also affect the process of reconciliation within the Cambodian society. The aim of this paper is therefore to investigate the association between symptoms of prolonged grief and attitudes towards reconciliation. Methods. A sample of 775 survivors of the Khmer Rouge regime who lost relatives during the conflict were interviewed about their losses and traumatic events, prolonged grief (PG; Complicated Grief Assessment Self-Report, CGA-SR), posttraumatic stress disorder (PTSD Checklist - Civilian Version) and attitudes towards reconciliation (Readiness to Reconcile Inventory, RRI). Results. A higher symptom severity of PG was significantly associated with readiness to reconcile even when controlling for other relevant variables (β = - 0.22; p < .001). Persons who met caseness criteria for PG were significantly less ready to reconcile, t(773) = 5.47, p < .001, than persons who did not meet caseness for PG. Conclusion. PG seems to be a relevant mental health correlate of attitudes towards reconciliation. The results of the current study underline the importance of also considering PG with regard to the reconciliation process in Cambodia and possibly also in other post-conflict regions.